Engravings and visual history in eighteenth-century Britain - Baudino, Isabelle (New York, NY : Routledge, 2023)
"Extending the scholarly discussion of visual history, this book examines eighteenth-century engraved book illustrations in order to outline the genealogy of the modern visualization of the past in Britain. This study is based on a body of more than a hundred engraved historical plates designed in the second half of the eighteenth century in Britain and published in more than a dozen pictorial histories. Focusing on these previously unstudied engravings, this work contributes to the study of eighteenth-century visual culture and is informed by current interdisciplinary approaches at the intersection of visual and book studies. This book is about the urge to envision the past and about the establishment of the new relationship between visual media, visuality and history in eighteenth-century Britain. The book will be of interest to scholars working in art history, British history, book studies, and visual culture"--
Keywords: Prints, British -- 18th century -- Themes, motives; History in art; Illustration of books -- Great Britain -- 18th century; Art and society -- Great Britain -- History -- 18th century; ART / Techniques / Printmaking; ART / European